A Sancta Sapientia Medieval: enigma e mistério no teatro cristão de Rosvita de Ganderseheim - Martins, Gilberto Figueiredo [UNESP] (2011)
Within the scope of Literary Studies, theory, criticism, and historiography about the literature produced in the Middle Ages developed considerably from 1940 on, with the works of Ernst Curtius, Mikhail Bakhtin, and Erich Auerbach. In spite of the progress made, some specific aspects remain in the shadow, with incursions which were punctual though meaningful: that is the case of the critic fortunes about women‟s literary production in that period. Rosvita was a canoness and lived in the Benedictine convent of Gandersheim (Germany), in the 10th century A.D. Coming under Terence‟s influence, she wrote theater plays in Latin in which she figuratively presented theological issues in order to spread the Christian doctrine. The martyrdom issue deserved to be put in relief and was the focal point of the play Wisdom, which took place at the time of the Roman emperor Adrian. This paper analyzes that dramatic text discussing, at the end, how the categories of symbol, enigma, allegory, and mystery are organized by the author as expressive resources and structural elements.